2022
DOI: 10.1210/jendso/bvac117
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Burden of Weekly Somatrogon vs Daily Somatropin in Children With Growth Hormone Deficiency: A Randomized Study

Abstract: Context Somatrogon is a long-acting recombinant human growth hormone treatment developed as a once-weekly treatment for pediatric patients with growth hormone deficiency (GHD). Objective Evaluate patient and caregiver perceptions of the treatment burden associated with the once-weekly somatrogon injection regimen vs a once-daily Somatropin injection regimen. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…This result is consistent with data from a previous discrete choice experiment study having showed that patients prefer a less frequent injection regimen for treating GHD ( 31 ). Our mean overall life interference total score related to daily injections of somatropin was consistent with the one found in the NCT03831880 trial (27.7 and 24.13), and three times higher than the mean score related to weekly injections of somatrogon (8.63, P < 0.0001 between groups) ( 17 ). As reported in other conditions, a reduced treatment burden may result in improvement treatment adherence ( 12 ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This result is consistent with data from a previous discrete choice experiment study having showed that patients prefer a less frequent injection regimen for treating GHD ( 31 ). Our mean overall life interference total score related to daily injections of somatropin was consistent with the one found in the NCT03831880 trial (27.7 and 24.13), and three times higher than the mean score related to weekly injections of somatrogon (8.63, P < 0.0001 between groups) ( 17 ). As reported in other conditions, a reduced treatment burden may result in improvement treatment adherence ( 12 ).…”
Section: Discussionsupporting
confidence: 88%
“…After first results from a crossover phase III trial which showed that treatment burden of weekly injections of somatrogon was lower than that of somatropin administered once daily in children with GHD (NCT03831880 trial) ( 17 ), the real-world cross-sectional French QOLITHOR study, conducted in 275 pediatric patients including 166 children with GHD, provides complementary information on patient experience as recommended by French, European, and US Health Authorities ( 18 , 19 , 20 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-acting GH preparations (LAGH), injected once weekly as opposed to once daily, have recently been approved for use in the US, EU, Japan, Canada, and Australia and are believed to be a potential solution for improvements in patient adherence ( 18 ). Although no published data have emerged on the impact of LAGH on adherence from real-world use, a recently published clinical trial demonstrated that treatment burden, as evaluated by life interference, was significantly reduced when patients were treated with somatrogon once weekly compared to once daily Genotropin, and the overall treatment experience for somatrogon was preferred by patients and caregivers ( 19 ). Another recent study found a preference for LAGH and reduced treatment burden in patients that switched from daily somatropin to weekly lonapegsomatropin ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Factors contributing to poor adherence include the burden of daily injections, pain caused by injections, storage issues, the need to reconstitute solutions, and managing injections while traveling ( 6 , 12 , 13 ). There is, therefore, a need for GH therapies that require a reduced injection frequency, while still being effective and having a tolerable safety profile compared to daily hGH ( 14 ).…”
Section: Introductionmentioning
confidence: 99%